STUDI KORELASI TENTANG KENAKALAN SISWA DENGAN PRESTASI BELAJAR SISWA SMP NEGERI 1 AROSBAYA BANGKALAN - Shodiq, Ja’far; Yaroh, Siti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to analyze and explain the Correlation Study of Student Delinquency and Student Achievement at SMP Negeri 1 Arosbaya with a focus on discussing the definition of student delinquency and learning achievement. The method used in this research is descriptive qualitative with data collection techniques, namely observation, interviews, documentation and questionnaires. In this research, it was formulated that there is a correlation between student delinquency and learning achievement. The object of this research is SMP Negeri 1 Arosbaya. From the analysis results, it was concluded that there was a significant negative correlation between naughty students and learning achievement at SMP Negeri 1 Arosbaya Bangkalan